Vegetation Structure and Diversity of Mangrove Species in The Bagek Kembar Natural Forest, Sekotong, West Lombok - Hidayat, XZardht Alex; Arifin, Rizki Dewi Sativa Lestari; Syukur, Abdul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Mangroves are a community or individual plants that live with special adaptations and form vegetation structures at the tide lines. This research aims to analyze the composition and structure of natural mangrove vegetation in the Bagek Kembar mangrove forest, Sekotong, West Lombok. Data collection used line transect and quadratic methods. The structure and composition of mangrove forest vegetation were analyzed based on density, frequency, dominance, importance value index, Shannon-Wiener diversity index (H'), species richness index (R), and evenness index (S). The research results show that the structure and composition of the natural Bagek Kembar mangrove consists of 10 species and 4 families. The highest importance index value was obtained for the Avicennia marina species with a value of 151.52 for the tree category, 172.16 for the sapling category, and 99.59 for the seedling category. The mangrove diversity index at all growth levels is included in the medium category. The species richness index at the tree growth and sampling levels is in the medium category, but at the seedling growth level it is in the low category. The evenness index at all growth levels is in the fairly even category. Furthermore, the highest density at all growth levels was obtained from the seedling level, followed by saplings and trees. The diameter class density shows an inverted “J” curve which indicates that the forest is in natural condition. Based on the research results, it can be concluded that the structure and composition of mangroves in the Bagek Kembar natural forest has a fairly stable ecosystem condition. Conservation efforts need to be increased to improve environmental sustainability.